MENIKAH DENGAN KAUM KERABAT DAN PENGARUHNYA BAGI ANAK–ANAK - Oktavia Wahyu Utami (Universitas Muhammadiyah Surakarta, 2020)
The purpose of writing is to know, describe, analyze and provide knowledge to the public about the consequences of being married to relatives and the influence on their children in the future. The consequences of marrying relatives include the easy transmission of inherited diseases to the resulting children and an increase in the number of inherited diseases among family members. There is a lot of evidence that explains that marriage with relatives can cause deafness, discoloration, mute and many others. In the Al-Qur'an and Hadiths, it has been explained about the recommendation to avoid marriage with relatives. To avoid the transmission of various types of inherited diseases, we should look for a life partner not from close family. Exo Because we as humans should follow the orders of Allah and the Prophet and stay away from the prohibitions, so that we can be safe in the world and the hereafter.